Gastric juice MicroRNAs as potential biomarkers for the screening of gastric cancer. Issue 9 (18th January 2013) - Cui, Long; Zhang, Xinjun; Ye, Guoliang; Zheng, Tuo; Song, Haojun; Deng, Hongxia; Xiao, Bingxiu; Xia, Tian; Yu, Xiuchong; Le, Yanping; Guo, Junming
Abstract BACKGROUND: MicroRNAs (miRNAs) play a crucial role in carcinogenesis; however, it largely remains unclear whether miRNAs in gastric juice, which is specific for gastric tissues, can be used as biomarkers for gastric cancer. The objective of the current study was to investigate the feasibility of using gastric juice miRNAs as potential biomarkers to assist in screening for gastric cancer. METHODS: Gastric juice samples were collected from 141 patients who underwent upper gastrointestinal endoscopy examination between September 2010 and December 2011. Gastric cancer and adjacent normal biopsy specimens also were collected. The existence and stability of miRNAs in gastric juices were determined by real‐time reverse transcriptase‐quantitative polymerase chain reaction (RT‐qPCR) and sequencing. miRNA levels in tissues and gastric juices were detected by RT‐qPCR. A receiver operating characteristic (ROC) curve was constructed for differentiating gastric cancer from benign gastric diseases. RESULTS: Levels of miRNA‐21 (miR‐21) and miR‐106a in gastric cancer tissues were significantly higher compared with the levels in adjacent tissues (P = .006 and P = .001, respectively). Patients who had gastric cancer had significantly different levels of gastric juice miR‐21 and miR‐106a compared with patients who had benign gastric diseases (both P < .001). There were significant correlations between miR‐21/miR‐106a levels and Borrmann types. miR‐21 levels in intestinal type gastric cancer specimens were higher than that in diffuse (P = .003) or mixed (P < .001) gastric cancer types. The area under the ROC curve was up to 0.969 for miR‐21 and 0.871 for miR‐106a. CONCLUSIONS: The current results indicated that certain miRNAs in gastric juice are potential biomarkers that can assist in screening for gastric cancer. Cancer 2013. © 2013 American Cancer Society.